2021
DOI: 10.1136/bmjopen-2020-041919
|View full text |Cite|
|
Sign up to set email alerts
|

Association between serum uric acid and obesity in Chinese adults: a 9-year longitudinal data analysis

Abstract: ObjectivesHyperuricaemia has been reported to be significantly associated with risk of obesity. However, previous studies on the association between serum uric acid (SUA) and body mass index (BMI) yielded conflicting results. The present study examined the relationship between SUA and obesity among Chinese adults.MethodsData were collected at Guangdong Second Provincial General Hospital in Guangzhou City, China, between January 2010 and December 2018. Participants with ≥2 medical check-up times were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
4
24
0
1
Order By: Relevance
“…Our present results found that the PCOS patients with hyperuricemia were prone to be obese, which was consistent with a previous study that a high SUA level had a significant association with the increased risk of obesity ( 29 ). After adjusting for BMI, the group of PCOS patients with hyperuricemia had significantly higher WHR, TC, and LDL-c than the non-hyperuricemia group.…”
Section: Discussionsupporting
confidence: 94%
“…Our present results found that the PCOS patients with hyperuricemia were prone to be obese, which was consistent with a previous study that a high SUA level had a significant association with the increased risk of obesity ( 29 ). After adjusting for BMI, the group of PCOS patients with hyperuricemia had significantly higher WHR, TC, and LDL-c than the non-hyperuricemia group.…”
Section: Discussionsupporting
confidence: 94%
“…Uric acid is excreted mainly via the kidney 3 . Many factors affect circulating uric acid levels, such as age, sex, ethnicity, body mass index 4 7 as well as lifestyle factors including alcohol consumption, smoking, and physical activity 6 , 8 , 9 . In addition, kidney disease can impair the excretion of uric acid by the kidney and thus can increase uric acid levels in the circulation 6 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia can cause the saturation of the weakly water-soluble urate salt and precipitate out in the form of monosodium urate crystals, causing kidney stones and gout. In addition, hyperuricemia is also closely related to many diseases including hypertension [ 3 ], major cardiovascular and coronary events [ 4 ], type 2 diabetes [ 5 ], chronic kidney disease [ 6 ], obesity [ 7 ], and metabolic syndrome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia can cause the saturation of the weakly water-soluble urate salt and precipitate out in the form of monosodium urate crystals, causing kidney stones and gout. In addition, hyperuricemia is also closely related to many diseases including hypertension [3], major cardiovascular and coronary events [4], type 2 diabetes [5], chronic kidney disease [6], obesity [7], and metabolic syndrome [8]. e triglyceride-glucose (TyG) index was first reported in 2008 [9] and compared with the HOMA-IR index, indicating that the TyG index can be used as a reliable, inexpensive, and simple substitute for insulin resistance [10,11].…”
Section: Introductionmentioning
confidence: 99%